The Six Thinking Hats (STH) Strategy to Improve Students’ Speaking Achievement in Merdeka Curriculum - Tefanya Laili Mukhibbah; Endang Mastuti Rahayu (Faculty of Culture, Management, and Business Universitas Pendidikan Mandalika (UNDIKMA), 2024)
The purpose of this study was to illustrate how the use of six thinking hats strategy to improve students' speaking achievement in Merdeka curriculum. Many students had difficulties speaking English because lacking self-confidence, lacked practice, and teacher not used learning strategies to attract students to learn to speak. In the Merdeka curriculum era, teacher must choose appropriate learning strategies for teaching speaking. One type of strategy was the six thinking hats strategy, because it could be interesting and encourage students to learn or practice speaking. This study was classroom action research. The research subject was the 10th grade of students at SMA 5 Wachid Hasyim Surabaya. Which consisted of 36 students. In this research, researchers used subjective tests, observation sheets, and questionnaires to collect data which were analyzed quantitative and descriptive qualitative. The results of the subjective test was 36 students got a score of 14% in the pre-test, 64% in cycle 1, 86% in cycle 2, these results showed that the students were able to improve their speaking achievement. The results of observational showed that six thinking hats was strategy used in learning to make students active. The results of the questionnaire showed that 50% of students agree with the six thinking hats strategy was an effective strategy for improving students' speaking achievement. The conclusion was that six thinking hats strategy can be used in teaching speaking, because students were more active in practicing speaking, fun and was a successful strategy to improving speaking achievement.